Dapatkah Desain Produk Kuliner Aceh Mengurangi Emisi Karbon dan Melestarikan Kearifan Lokal? - Yusmaneli (Design Journal, 2025)
This study examines the potential of Acehnese culinary product design in reducing carbon emissions while maintaining local wisdom. The focus of the study is on identifying product design innovations that support decarbonization without ignoring the characteristics of regional culinary culture. The case study method and literature review reveal that the application of green technology and sustainability principles can reduce the environmental impact of the Acehnese culinary industry, while maintaining traditional values. The results of the analysis show that the synergy between environmentally friendly technology, production process innovation, and the use of local ingredients has the potential to create a low-carbon culinary ecosystem. These findings recommend an integrative strategy for industry players in achieving sustainability targets while strengthening cultural identity.